Copro-ELISA Prevalence of Fasciola hepatica in Cattle in Van, Turkey - Bostanci, Aysegul; Oğuz, Bekir (Acta Scientiae Veterinariae, 2017)
Background: Fasciolosis is an important food borne zoonotic disease caused by Fasciola trematode parasites. There are two types of Fasciola spp. namely F. hepatica and F. gigantica, widely distributed across the globe, affecting both human and animal hosts. In endemic regions, it is possible to base the diagnosis of fasciolosis on clinical signs and the season, however, it could be more useful to support these data with fecal examination and various hematologic and serological tests. The aim of this study was to determine the prevalence of fasciolosis in cattle in Van province by copro-ELISA technique. Materials, Methods & Results: Fecal samples from 140 cattle were technically collected and examined by sedimentationzinc sulphate flotation technique. Modified McMaster sedimentation technique was applied to the egg positive samples to determine the EPG values. Fasciola hepatica coproantigens in samples were investigated by ELISA. The coprological and antigen ELISA prevalence of fasciolosis were determined as 5.07% and 30.7%, respectively, which shows the significant difference between these methods in examining the rate of infection. The highest prevalence of fasciolosis infection was observed in 1-2 age groups (41.9%), and this prevalence was followed by 3-5 (31.2%) and ≤6 age group (5%). The differences between age groups were found significant (P < 0.05). The prevalence in female and male cattle was found as 30.1% and 35.3% This difference was not found statistically significant (P > 0.05). The highest prevalence was observed in Brown Swiss with the ratio of 40% and this was followed by 31% in Crossbreed and 22.6% in Rubia Gallega. The differences among breeds were not statistically significant (P > 0.05). Discussion: Fasciola hepatica is the most common species of liver flukes, and its pathogenicity leads to significant impact on the economy of the livestock industry. The economic losses consist of costs of anthelmintics, drenches, labor, liver condemnation at meat inspection; and losses in production due to mortality, reduction in meat, milk and reduction in growth rate, fertility and decreased feed intake, conversion and lower resistance to other disease.To diagnose fasciolosis, eggs can only be detected in feces after the tenth or twelfth week of infection once the parasites have matured. It is reported that routine microscopic methods used before this stage do not provide sufficient information about the current infection status. Therefore, serological tests have been introduced for the early diagnosis of the disease. Among these tests, the ELISA test based on detecting antigens has become the most commonly used test. It is known that the probability of ELISA to cross-react with parasites that carry similar immunogenic features and the similarities between antibodies generated in previous infections and new infections pose a challenge to making the definitive diagnosis. Therefore, it is reported that to predict the parasitic potential of the host and the success of treatment beforehand, the presence of Fasciola spp. antigens can be investigated in serum instead of antibodies. In conclusion, this study has established prevalence of fasciolosis in cattle raised in Van province using the copro-ELISA technique for the first time. It has been concluded that copro-ELISA could serve as a useful technique for herd diagnosis of fasciolosis in cattle in addition to fecal examinations particularly with respect to fasciolosis.